The Application of Article 22 to Bid-Rigging Practices in High-Technology Procurement: The BRIN Case - Samuel Febrian Prima; Grace Sharon (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2026)
This study examines the application of Article 22 of Law No. 5 of 1999 in KPPU Decision No. 02/KPPU-L/2024 concerning BRIN’s procurement of Cryo-Electron Microscope and Transmission Electron Microscope equipment, and its annulment by the Central Jakarta Commercial Court in Decision No. 5/Pdt.Sus-KPPU/2024. It focuses on whether the elements of bid-rigging, especially agreement or concerted practice and conduct intended to determine the tender winner, were sufficiently proven. Using a normative juridical method, this article analyzes statutory rules, procurement regulations, KPPU guidelines, court reasoning, and open-access competition law literature. The study finds that many indicators relied upon by KPPU were technical rather than competitive in nature. In high-technology procurement, similarities in bid documents may result from manufacturer specifications, compatibility requirements, limited suppliers, and standardized technological systems. The Court emphasized that indirect evidence must be supported by behavioral or economic indicators, such as abnormal pricing, complementary bidding, bid rotation, or coordinated strategy. The article argues that Article 22 enforcement in technology-intensive procurement should distinguish technical alignment from collusion and apply a structured evidentiary framework combining economic and technological analysis. This approach promotes legal certainty while preserving cartel enforcement in specialized public procurement markets and preventing over-enforcement.